Effect of national holidays on health outcomes of patients receiving peritoneal dialysis in a single center over a ten-year period. Issue 1 (31st December 2023) - Yang, Wei; Zeng, Li; Yang, Huibin; Guo, Fujia; Zhou, Dan; Cui, Wenting; Wu, Shuran; Chen, Cong; Zhao, Jiayao; Wang, Weidong; Yang, Ning; Lin, Hongli; et al.
Abstract: Background: National holidays are associated with high mortality in some diseases, but little is known about patients undergoing peritoneal dialysis (PD). The research aimed to investigate the impact of national holidays on the health outcomes of PD patients. Methods: Over ten years, all episodes of unplanned hospitalization, death, and peritonitis in PD patients were collected in our center. Seven national holidays in China were chosen, and non-holiday days were selected as the control period. The effect of national holidays was observed by comparing the hospitalization, death, and peritonitis rates between holiday and non-holiday groups. Results: There were 297 events in all holiday periods and 1247 in non-holiday periods. There is no significant difference in hospitalization rate between holiday and non-holiday groups (32.4% ± 6.4% vs. 29.2% ± 3.4%, p = 0.175). So is the death rate [6.3% (4.8–12.3%) vs.5.0% (4.2–8.9%), p = 0.324] and peritonitis rate [0.19 (0.13–0.53) vs. 0.22 (0.18–0.27), p = 0.445] between the two groups. Significant differences were observed in the distribution of peritonitis causes between the two groups ( p = 0.017). The rate of secondary to other infections in the holiday group was significantly higher than in the non-holiday group (25.0 vs. 10.3%, p = 0.015). Conclusion: Our study suggested no national holiday effect on health outcomes of PD patients based on ten-year data in our center.